2021
DOI: 10.3390/jmmp5020049
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Components Manufactured by a Sheet-Bulk Metal Forming Process

Abstract: Due to rising demands regarding the functionality and load-bearing capacity of functional components such as synchronizer rings in gear systems, conventional forming operations are reaching their limits with respect to formability and efficiency. One way to meet these challenges is the application of the innovative process class of sheet-bulk metal forming (SBMF). By applying bulk forming operations to sheet metal, the advantages of both process classes can be combined, thus realizing an optimized part weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The paper [3] provided an innovative of sheet-bulk metal forming (SBMF) process. It found that the hardness distribution and homogeneity of the forming parts are improved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper [3] provided an innovative of sheet-bulk metal forming (SBMF) process. It found that the hardness distribution and homogeneity of the forming parts are improved.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…For comparison purposes, the results obtained by [3] approved that the hardness homogeneity distribution can be improved and the process failures can be prevented in a forming process (Functional Analysis). These findings are matching with the results obtained here.…”
Section: Fig 19 Energy-time Relationshipmentioning
confidence: 99%